Biophysical profile and modified biophysical profile in predicting the fetal outcome - Vanamala, V. G.; Rachel, Aruna; Pakyanadhan, Sushil; Abraham P., Sudheep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Baby’s well-being in utero is often done by using a cardiotocograph (CTG) machine, which assesses the baby’s heart beat pattern as well as the mother’s uterine contractions. However, lowered fetal movements sometimes may be fatal for the baby. Thus, the biophysical and the modified biophysical profile have been introduced. Methods: 242 patients with over 34 weeks of gestation and with one or more risk factors were included in the study. After taking the demographic details, the patients were subjected to detailed physical and clinical evaluation. Modified BPP was done on all the patients. Index of acute fetal hypoxia the NST was done along with the cardiotocograph (CTG). Amniotic fluid volume was calculated. Results: According to the fetal non-stress test, majority of the patients (70.7%) were reactive while 29.3% were non-reactive. Most of the patients had an amniotic fluid index in the normal range i.e. between 8 -<25, 18.6%) had an AFI value of <6 cm while 13.6% had between 6 - <8. Among the babies with reactive NST, non-reactive NST and AFI ≤5, the most common outcome was low birth weight. APGAR score <7 was observed in 11.1%, 13.1%, 20% among Reactive NST, Non-reactive NST and AFI ≤5 respectively. Conclusions: Present study shows that BPP and MBPP are both comparable to each other, therefore, MBPP, being an easier test can be substituted for BPP.